The European videogame: An introduction to its history and creative traits - Pérez Latorre, Óliver (European Journal of Communication, 2013)
This article presents the main findings of research into the history and creative characteristics of the European videogame. Faced with the long hegemony of the US and Japan in the videogame industry, it is necessary for Europe to become more aware of its role in this sector and determine its aspirations and plans for the future. To do this, it is vital to deepen our knowledge of European videogame history and its main ‘actors’ (designers, development studios, publishers) as well as the creative traits of European videogame production. This article aims to contribute to raising this awareness. The research employs two complementary approaches, first a survey of the historiographic literature on videogames and second, an analysis based on game design theory, in order to gain a wide overview of the subject.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMjY3MzIzMTEzNDc3MzY1